Impact of in vitro HIV infection on human thymic regulatory T cell differentiation - Swaminathan, Sharada; Scorza, Tatiana; Yero, Alexis; Farnos, Omar; Burke Schinkel, Stephanie C.; Angel, Jonathan B.; Jenabian, Mohammad-Ali (Frontiers in Microbiology, 2023)
Background: The differentiation and function of immunosuppressive regulatory T cells (Tregs) is dictated by the master transcription factor FoxP3. During HIV infections, there is an increase in Treg frequencies in the peripheral blood and lymphoid tissues. This accentuates immune dysfunction and disease progression. Expression of FoxP3 by thymic Tregs (tTregs) is partially controlled by TGF-β. This cytokine also contributes to Treg development in the peripheral blood and lymphoid tissues. Although TGF-β mediates lymphoid tissue fibrosis and peripheral Treg differentiation in HIV-infected individuals, its role in the induction and maintenance of Tregs within the thymus during HIV infection remains unclear. Methods: Thymocytes were isolated from fresh human thymic tissues obtained from pediatric patients undergoing cardiac surgery. Infection by both R5- and X4-tropic HIV-1 strains and TGF-β treatment of human thymocytes was performed in an in vitro co-culture model with OP9-DL1 cells expressing Notch ligand delta-like 1 without TCR activation. Results: Despite high expression of CCR5 and CXCR4 by tTregs, FoxP3+CD3highCD8- thymocytes were much less prone to in vitro infection with R5- and X4-tropic HIV strains compared to FoxP3-CD3highCD8- thymocytes. As expected, CD3highCD4+ thymocytes, when treated with TGF-β1, upregulated CD127 and this treatment resulted in increased FoxP3 expression and Treg differentiation, but did not affect the rate of HIV infection. FoxP3 expression and Treg frequencies remained unchanged following in vitro HIV infection alone or in combination with TGF-β1. Conclusions: FoxP3 expression and tTreg differentiation is not affected by in vitro HIV infection alone or the combination of in vitro HIV infection and TGF-β treatment.